How population size affects power-sharing: a comparison of Nigeria and Suriname. Issue 3 (27th May 2021) - Veenendaal, Wouter; Demarest, Leila
ABSTRACT: Theories on consociationalism and power-sharing posit that such arrangements are more likely to succeed in small societies. A small population size would produce close-knit, personal relations between political elites from different groups, resulting in consensual political relations. However, the empirical basis for these arguments is very shallow, as size effects have not been systematically analysed. In this paper we conduct a comparison of power-sharing politics in Nigeria and Suriname, which are the largest and smallest countries in the world that have implemented such arrangements. We find that informal power-sharing practices in both countries are remarkably similar: political elites rely on patron-client networks to maintain support, while inter-elite relations in both countries are strongly adversarial. Instead, we find that the main difference between the countries is in fact institutional in nature: in Nigeria power-sharing is enforced by strict formal rules, while Suriname has a very weak formal framework to engender power-sharing.